Integration of Gender Equality in Islamic Education Curriculum: A Content Study on Elementary School Textbooks - Fitria, Nur Annisa; Arif, Muhammad Syaikhul; Muhid, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to explore the extent to which the principle of gender equality has been integrated in Islamic Religious Education textbooks at the elementary school level. The focus of the analysis is on the representation of the roles of men and women in the teaching materials used in the independent curriculum. The main data in this study are six Islamic Religious Education and Budi Pekerti textbooks for Grades 1 to 6, published by the Center for Curriculum and Bookkeeping, Research and Development, and Bookkeeping Agency, Ministry of Education and Culture of the Republic of Indonesia. These books include Islamic Religious Education and Ethics for Primary School Grade 1 by Muhammad Nurzakun and Joko Santoso in 2021, Islamic Religious Education and Ethics for Primary School Grade 2 by A. Zainal Abidin and Siti Kusrini in 2021, and Islamic Religious Education and Ethics for Primary School Grade 3 by Moh. Ghozali and Erwin Wasti in 2022, the book Islamic Religious Education and Ethics for Primary 4 by Ahmad Faozan and Jamaluddin in 2021, the book Islamic Religious Education and Ethics for Primary 5 by Soleh Baedowi and Hairil Muhammad Anwar in 2021, and the book Islamic Religious Education and Ethics for Primary 6 by Nazirwan and Kholili Abdullah in 2022. This research uses a qualitative method with content analysis of the text and illustrations of Islamic Religious Education textbooks. The results of this study show a consistent pattern of gender bias, where male characters are dominant in religious and social roles, while female characters tend to be passive and limited to domestic roles. So then it is necessary to reformulate the content of the textbook to be more responsive to gender, in order to realize a fair Islamic education in accordance with the value of rahmatan lil 'alamin.